Efficient Exam Correction at Scale: Streamlining Paper-Based Assessments with the VoLl-KOrN System - Betzendahl, Jonas; Lohr, Dominic; Berges, Marc-Pascal; Kohlhase, Michael (Digitales Lehren und Lernen an der Hochschule Strategien - Bedingungen - Umsetzung, 2025)
This paper introduces VoLl-KOrN – a tool designed for digitizing and optimizing paper-based examination processes at universities. By utilizing QR codes on exam papers, VoLl-KOrN allows for submissions to be scanned and automatically assigned to students. The web interface allows educators to view, organize, and assess scanned exams. Its innovation lies in its use of answer classes that cluster similar responses, allowing automatic or manual scoring with a focus on objectivity and consistency. Additionally, the system enables a systematic analysis of exam data to improve teaching strategies and identify learning gaps. This enables further opportunities like interconnecting with learning platforms to, e.g., update a learner model based on exam performanc
Keywords: Assessment; Answer classes; learning analytics; educational technology; digital teaching; learner model